The Development of Ukrainian Electric Power Engineering Terminology: The “Golden Decade” - Liliia Kharchuk (Українознавство, 2018)
The objective of this work is to analyze the inception process of the Ukrainian electric power engineering terminology (UEPET). The task is to analyze one of the developmental stages of UEPET – the basis of the UEPE terminology system, known as the “Golden Decade”. In order to achieve this goal, we researched and outlined timelines of this stage in UEPET development, as well as analyzed the source and course of development and accession of UEPET during the aforementioned period. Research has shown that the second stage of UEPET formation took place during the 1920s and 1930s. Substantiation of UEPET occurred throughout this timeframe. The 1920s formed a decade of rapid evolution of electric power engineering in Ukraine. At that time, outstanding achievements of academic electric power engineers in connection with the emergence of new terminology caused a sudden demand for compilation and normalization of a national terminological system. At the beginning of 1925, the Technical Department of Ukrainian Academic Language established an electrical engineering section. This work attracted leading scholars, who created registers of terminology and also derived terms and lexical material from professional literature, dictionaries, and literary sources. UEPET formed at the beginning of the 1930s a conceptual terminological database, which reinforced a need for scholars. The lexicographical work of M. Darmoros, L. Darmoros, V. Dubrovskyi, K. Polonoskyi, F. Kalynovych, K.Turkalo, and other scholars, devoted to the terminology of other sectors, did not overlook the terminological lexicon that served the field of electric power engineering during this developmental phase. “Dictionary of Technical Terminology (General)” by I. Sheludko, T. Sadovskyi and “Dictionary of Technical Terminology (Electrical Engineering)” by I. Sheludko became the basis for modern UEPET. These works in terminography are, in our opinion, the greatest achievement in Ukrainian electric power engineering lexicography of the first half of the 20th century.